1991
DOI: 10.1620/tjem.165.165
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Proteinase Inhibitors on Polymorphonuclear Neutrophil Polarization.

Abstract: Polarization of polymorphonuclear neutrophils (PMNs) can be elicited by the chemotactic peptide N-formyl-methionyl-leucyl-phenylalanine (fMLP) and the microtuble-disrupting compound colchicine. Here we report on whether natural and synthetic proteinase inhibitors alter the polarizing response to these two agents. The crl-proteinase inhibitor, N-tosyl-L-phenylalanine chloromethyl ketone, and N"-tosyl-L-lysine chloromethyl ketone suppress fMLP-induced polarization and locomotion in a dose-dependent fashion, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…These results suggest that elastase plays a major regulatory role in chemotaxis in vitro . This contention is corroborated by previous reports showing that pharmacologic inhibition of elastase by L658758, Eglin C, or SLPI also blocks chemotactic neutrophil functions according to migration induced by PAF, f MLP or IL-8 [49][51]. While the mechanism is not precisely understood, blockade of cell surface proteinases inhibits intracellular signal for cytoskeletal change and polarization [49].…”
Section: Discussionsupporting
confidence: 77%
“…These results suggest that elastase plays a major regulatory role in chemotaxis in vitro . This contention is corroborated by previous reports showing that pharmacologic inhibition of elastase by L658758, Eglin C, or SLPI also blocks chemotactic neutrophil functions according to migration induced by PAF, f MLP or IL-8 [49][51]. While the mechanism is not precisely understood, blockade of cell surface proteinases inhibits intracellular signal for cytoskeletal change and polarization [49].…”
Section: Discussionsupporting
confidence: 77%
“…AAT is a major circulating serpin with relatively high homology to other angiostatic serpins, such as PEDF (42%) 20. AAT inhibits neutrophil polarization21 and chemotaxis 22…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the inhibitory effect of native M-AAT on neutrophil chemotaxis was first documented in 1973, when Ward and Tallemo stated that AATD sera lacked an ''inactivator'' of neutrophil chemotaxis (Ward and Talamo 1973). More recent evidence has shown that M-AAT is a potent inactivator of fMLP induced neutrophil chemotaxis (Stockley et al 1990), in part thought to be due to its ability to inhibit protease involvement and thus effecting downstream events, such as cytoskeletal change and polarisation (Aoshiba et al 1991). This latter phenomenon is further supported by a recent study illustrating the ability of AAT to inactivate calpain-1 activity thereby inhibiting neutrophil directional migration (Al-Omari et al 2011).…”
Section: The Use Of Aat Augmentation Therapy In Treatment Of Lung Dismentioning
confidence: 99%